2020
DOI: 10.29188/2222-8543-2020-13-4-30-34
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical efficacy of holmium and thulium ureterolithotripsy

Abstract: Introduction. Urolithiasis is one of the most common pathologies in modern urology. This disease is registered in 10% of the population and is manifested by an annual increase. Despite all the effectiveness and safety of Ho:YAG, in recent years, the thulium laser has attracted more and more interest. At the moment, in the modern literature there is not enough information about thulium and holmium ureterolithotripsy. The aim of this study is to compare the effectiveness of thulium and holmium ureterolithotrips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Furthermore, 30 articles were excluded because they did not meet the inclusion criteria. The final 13 studies [ 21 33 ], including 1394 patients, were included in this meta-analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 30 articles were excluded because they did not meet the inclusion criteria. The final 13 studies [ 21 33 ], including 1394 patients, were included in this meta-analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the perioperative outcomes, 11 studies [ 21 28 , 30 , 32 , 33 ] reported data on operation time, 8 studies [ 21 23 , 26 , 29 31 , 33 ] reported laser time data, 4 studies [ 21 23 , 25 ] reported data on duration of hospital stay, 3 studies [ 21 , 22 , 25 ] reported the drop in hemoglobin, 5 studies [ 21 , 22 , 26 , 29 , 31 ] reported the total energy used in the lithotripsy process, and the remaining 3 studies [ 23 , 26 , 32 ] reported postoperative ureteral stenting rates. The findings suggested that the operation time of the TFL group was shorter than that of the Ho: YAG group [-5.47, 95% CI (-8.86, -2.08), P = 0.002].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 comparative studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], with 1698 cases (TFL, 708; Ho:YAG, 990), were included in the meta-analysis; six RCTs [18][19][20][21][22][23], five prospective [24,[27][28][29]31], and four retrospective cohorts [25,26,30,32]. Four studies were conducted in the United States [19,24,25,30], four in India [20,22,27,28], three in Russia [18,21,29], one in Norway [23], one in Italy [31], one in Canada [32] and one from an Asian-European multi-institutional initiative [26]. Most studies reported clinical outcomes from adult cohorts, while two reported on paediatric patients [25,26].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most studies reported clinical outcomes from adult cohorts, while two reported on paediatric patients [25,26]. In addition, two studies reported a comparative study of TFL vs Ho:YAG in the mini-percutaneous nephrolithotomy (PCNL) procedure [20,27], three exclusively involved ureteroscopy (URS) [21,28,29], and the remaining studies included flexible URS with retrograde intra-renal surgeries (RIRS). Two studies compared TFL with Ho:YAG with pulse modulation (MOSES) [19,27], while the other studies included Ho:YAG of low-(30-35 W) or high-power (100-120 W) capability with no pulse modulation.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation